Intercultural universities in Peru and their challenges - García Zárate, Óscar Augusto (2022)
Intercultural universities are a special type of university created by the Congress of the Republic in response to the demands of the country's indigenous peoples, both Andean and Amazonian. They are institutions different from conventional universities and promote an unrestricted respect for their own culture and social dynamics. They take on the great challenge of becoming tools to reduce the worrying gaps in access to higher education faced by our indigenous youth, which make us a country with little chance of solving crucial problems affecting ethnic groups under the threat of extermination of ancestral knowledge and traditions unique in the world. Intercultural universities are thus part of the productive system of the peoples and manage intercultural knowledge within the framework of a scientific and technological system that promotes the development of native cultures based on their own paradigms: "good living" for the Andean peoples; "full life" for the Amazonians.